Efforts to Improve Mental Health of the Elderly Through Healthy Elderly Gymnastics - Erik Adik Putra Bambang Kurniawan; Enik Listyaningsih (Bhakti Sabha Nusantara, 2024)
Introduction: Elderly people are people with an age group at risk of experiencing mental health problems. In general, after people enter old age, they experience decreased memory and activity. With the decline in these two functions, the elderly also experience changes in psychosocial aspects related to the personality of the elderly. Given the large number of elderly people, it is necessary to have maintenance, especially mental health maintenance. Community-based mental health services as an effort to improve the quality of mental health services in the community by maximizing all the potential that exists in the community. Various activities for the elderly or elderly have been proven to help improve their health physically and mentally. Of the various types of activities for the elderly, gymnastics is one of the choices. Objective: To screen for mental health problems in the elderly: depression and to improve the mental health of the elderly through healthy elderly exercise. Design/method/approach: The method used is screening and physical activity intervention: Elderly Gymnastics. Findings/results: Based on the screening results, the majority of respondents did not experience depression with a total of 23 respondents (76.67%), mild depression 6 respondents (20%) and moderate depression 1 respondent (3.33%). Based on the results of the elderly gymnastics intervention, it was found that 30 respondents (100%) chose the answer that they were happy with the gymnastics activities that had been carried out. Conclusion: Physical activity intervention: elderly gymnastics can be an effort to improve the mental health of the elderly.